Smoking may compromise physical function long before it kills you - Glei, Dana A.; Weinstein, Maxine (Frontiers in Public Health, 2023)
Although prior research has demonstrated an association between smoking and worse physical function, most of those studies are based on older people and do not evaluate whether the age-related increase in physical limitations differs by smoking history. We quantify how the magnitude of the smoking differential varies across age. This cohort study comprised a national sample of Americans aged 20-75 in 1995-96, who were re-interviewed in 2004-05 and 2013-14. Our analysis was restricted to respondents who completed the self-administered questionnaires at Wave 1 (N=6325). Follow-up observations for those respondents were included if they completed the self-administered questionnaires at Wave 2 (N=3929) and/or Wave 3 (N=2849). The final analysis sample comprised 13,103 observations over a follow-up period of up to 19 years (1995-2014). We used a linear mixed model to regress physical limitations on smoking status at baseline adjusted for sex, age, race, socioeconomic status, alcohol abuse, drug abuse, and obesity with an interaction between age and smoking to test whether the age pattern of physical limitations differed by smoking history. Additional models incorporated measures of smoking duration and intensity. In the fully-adjusted model, smokers exhibited a steeper age-related increase in physical limitations than never smokers. Thus, the disparities in physical limitations by smoking status widened with age but were evident even at young ages. The estimated differential between heavy smokers and never smokers rose from 0.24 SD at age 30 to 0.49 SD at age 80. At younger ages, heavy smokers who quit recently fared worse than current light smokers and not much better than current heavy smokers. We know smoking is bad for our health, but these results reveal that differences in physical limitations by smoking history are evident even at ages as young as 30. Physical limitations that emerge early in life are likely to have an especially large impact because they can jeopardize health for decades of remaining life. Smoking probably will not kill you at young age, but it may compromise your physical function long before it kills you. Just don't do it.